Streamlined and Robust Stage-Specific Profiling of Gametocytocidal Compounds Against Plasmodium falciparum - Reader, Janette; van der Watt, Mariette E.; Birkholtz, Lyn-Marié (Frontiers in Cellular and Infection Microbiology, 2022)
Malaria elimination is dependent on the ability to target both the pathogenic and transmissible stages of the human malaria parasite, Plasmodium falciparum. These forms of the parasite are differentiated by unique developmental stages, each with their own biological mechanisms and processes. These individual stages therefore also respond differently to inhibitory compounds, and this complicates the discovery of multistage active antimalarial agents. The search for compounds with transmission-blocking activity has focused on screening for activity on mature gametocytes, with only limited descriptions available for the activity of such compounds on immature stage gametocytes. This therefore poses a gap in the profiling of antimalarial agents for pan-reactive, multistage activity to antimalarial leads. Here, we optimized an effective and robust strategy for the simple and cost-effective description of the stage-specific action of gametocytocidal antimalarial compounds.